Vocabulary knowledge in the production of written texts: a case study on EFL language learners - Rodrigo Tovar Viera (Revista Tecnológica)
Vocabulary is essential in second and foreign language acquisition because without its appropriate and sufficient knowledge learners cannot understand others or express their own feelings. After a lengthy period of focusing on the development of grammatical competence, language instructors and researchers now recognize the importance of vocabulary learning. This paper examines how vocabulary knowledge influences in written production; it measured the lexical richness and lexical profile of argumentative essays written by EFL language learners. The instruments used in this study are the Vocabulary levels test and the Vocabprofile software, lextutor.ca. Data were collected from a quota sampling of 40 elementary learners who study English as foreign language. The results after the pedagogic intervention with a lexical approach revealed that the treatment group outperformed the control group in language production. The findings suggest that the vocabulary knowledge of foreign language is necessary; it provides learners a broader ability to produce well-structured written texts and contributes to the comprehension of utterances as well.